Dopamine D3 Receptor Antagonism Reverses the Escalation of Oxycodone Self-administration and Decreases Withdrawal-Induced Hyperalgesia and Irritability-Like Behavior in Oxycodone-Dependent Heterogeneous Stock Rats - de Guglielmo, Giordano; Kallupi, Marsida; Sedighim, Sharona; Newman, Amy H.; George, Olivier (Frontiers in Behavioral Neuroscience, 2020)
Prescription opioids, such as oxycodone, are highly effective analgesics for clinical pain management, but approximately 25% of patients who are prescribed opioids misuse them, and 5-10% develop an opioid use disorder. Effective pharmacotherapies for the prevention and treatment of opioid abuse and addiction need to be developed. The present study evaluated the effects of the highly selective dopamine D3 receptor antagonist VK4-116 on oxycodone addictive-like behaviors. We used a model of extended access to oxycodone self-administration and tested the effects of VK4-116 administration on the escalation of oxycodone selfadministration and withdrawal-induced hyperalgesia and irritability-like behavior in male and female rats. Pretreatment with VK4-116 (5-25 mg/kg, i.p.) dose-dependently decreased the escalation of oxycodone self-administration and reduced withdrawal-induced hyperalgesia and irritability-like behavior in opioid-dependent rats. These findings demonstrate a key role for D3 receptors in both the motivation to take opioids and negative emotional states that are associated with opioid withdrawal and suggest that D3 receptor antagonism may be a viable therapeutic approach for the treatment of opioid use disorder.